Some aspects of topology and kinematics of a 3DOF translational parallel mechanism - Bałchanowski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents elements of the topology, geometry and the kinematic analysis of a translational parallel mechanism with three degrees of freedom. In such mechanisms the selection of a proper structure and geometry ensures that the driven link maintains a fixed orientation relative to the base. The method of determination of the configuration of mechanisms using contour vector notation was elaborated in the paper. The equations for the analysis of the direct and inverse kinematics task are determined. An analytical procedure for determining the system?s singular positions is presented and illustrated with examples.
Keywords: the parallel mechanisms; topology; direct and inverse kinematic; singularities